Analyzing the issue of organizational commitment: Determining the mediating factor of Islamic work ethic / Zalinawati Abdullah and Associate Prof. Dr. Siti Haryati Shaikh Ali - Abdullah, Zalinawati; Shaikh Ali, Siti Haryati (Research Management Institute (RMI), 2014)
Every employee must give his full commitment to the organization. Employee commitment to organizations is the key to the success of an organization. There are many factors that motivate employees to give full commitment to the organization. For example, as a Muslim, the religion factor became the basic guide during work. This is because, in Islam, a job that is done with a condition of employment that does not contradict with Islam is a form of worship (Ibadah). Islamic work ethic is the ethic that is stated in the Quran and Sunnah. Islam is the comprehensive religious in the world. Islamic cover all the aspect included economic, human behaviour (akhlak), management, politic and many more.